-2=-1.6(x+8)

Simple and best practice solution for -2=-1.6(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2=-1.6(x+8) equation:


Simplifying
-2 = -1.6(x + 8)

Reorder the terms:
-2 = -1.6(8 + x)
-2 = (8 * -1.6 + x * -1.6)
-2 = (-12.8 + -1.6x)

Solving
-2 = -12.8 + -1.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.6x' to each side of the equation.
-2 + 1.6x = -12.8 + -1.6x + 1.6x

Combine like terms: -1.6x + 1.6x = 0.0
-2 + 1.6x = -12.8 + 0.0
-2 + 1.6x = -12.8

Add '2' to each side of the equation.
-2 + 2 + 1.6x = -12.8 + 2

Combine like terms: -2 + 2 = 0
0 + 1.6x = -12.8 + 2
1.6x = -12.8 + 2

Combine like terms: -12.8 + 2 = -10.8
1.6x = -10.8

Divide each side by '1.6'.
x = -6.75

Simplifying
x = -6.75

See similar equations:

| 3.4-8=4.6 | | 260+20x=140+30x | | -(2m-2)-2(1-4m)=12 | | 260x+20=140+30x | | 4a=1 | | -2r-8=-4 | | y=4*0-6 | | 13n-(-9)=-48 | | 8+2(x-12)=x+40 | | 260+20=140+30 | | 7-0.5x=2 | | 9Y=Y+8 | | 3x-3=22 | | 1.9=-0.95(x+6) | | x/3-5= | | 2(x)+2(12)=(x-2)+(x-2)+2(16) | | 3x^2-10x+20=x^2+3x | | 6x=21-1y | | 5x-3=5x+2 | | 6y=21-1y | | 4898*28= | | 0.6b+51=42-1.4b | | 2*1-y=-7 | | 6s+4(44.44)=3s+7(44.44) | | 2*0-y=-7 | | 5(3n-2)=6n-37 | | 4-12=h | | -7(x+1)=-21 | | 2400+60x=120x | | 2p+18=8 | | 12+(n-1)6=60 | | y=4*-1-6 |

Equations solver categories